Economic Evaluation of the Use of FeNO for the Diagnosis and Management of Asthma Patients in Primary Care in Sweden - Darbà, Josep (Clinicoecon Outcomes Res, 2021)
OBJECTIVE: To determine the economic impact of the fraction of exhaled nitric oxide (FeNO) in asthma diagnosis and management in primary care in Sweden. METHODS: An economic model has been developed to determine the economic impact of the fraction of exhaled nitric oxide (FeNO) in asthma diagnosis and management in primary care in Sweden. The model includes the use and cost of commonly used tests, the associated outcomes and diagnostic accuracy. We compared FeNO with spirometry and reversibility testing, methacholine challenge test, allergy testing, and blood eosinophil count. One-way sensitivity analyses were performed to confirm the robustness of results. RESULTS: Adding FeNO measurement in asthma diagnosis resulted in cost savings of SEK 672 per patient by the fourth year. The use of FeNO testing in asthma management proved to be a dominant strategy when compared with each other test except methacholine challenge test. Sensitivity analyses confirmed the robustness of the results. CONCLUSION: Introducing FeNO testing in clinical practice for the diagnosis and management of asthma in primary care in Sweden is less costly than standard methods while providing similar health benefits.